URGENSI PENCATATAN WAKAF MELALUI APLIKASI SISTEM INFORMASI WAKAF (SIWAK) DI KABUPATEN TEMANGGUNG PERSPEKTIF MASLAHAH MURSALAH - Khulifah, Umi (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines the urgency of recording waqf land through the Waqf Information System (SIWAK) application from the perspective of maslahah mursalah with a case study in Temanggung Regency. The background of the study departs from the weakness of manual waqf documentation which is vulnerable to loss and ineffective in protecting waqf assets. This study uses a qualitative method with a case study approach, through observation, interviews, and literature studies. The results show that SIWAK is a digital innovation that can increase the efficiency, transparency, and security of waqf data. The implementation of SIWAK is not only in line with the principles of maqashid al-shari'ah, but also in accordance with the fiqh rules of Dar'ul Mafasid wa Jalbul Mashalih and the principles of public policy in Tasharruf al-imam ‘ala al-ra'iyyah manuthun bi al-maslahah. SIWAK has proven to be a strategic instrument in maintaining the sustainability and benefit of waqf assets in the digital era.